Peripheral arterial occlusive disease and ischemic disease of the lower limbs are not the same condition. A proposed unambiguous Italian terminology for defining Peripheral arterial disease of lower limbs and related clinical/therapeutic implications - Simone Meini; Elio Melillo; Rino Migliacci; Gabriele Nicolosi; Grazia Panigada; Giancarlo Landini (Italian Journal of Medicine, 2014)
Not required